Additive of perovskite material, perovskite battery and preparation method
By adding trifluoroethanol as an additive to perovskite materials, the perovskite crystallization process and interface wetting are optimized, and the problem of insufficient SAM layer in trans perovskite solar cells is solved, which significantly improves perovskite Photovoltaic characteristics and stability of the battery.
Patent Information
- Application Number
- CN202411524882.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
AI Technical Summary
In trans perovskite solar cells, the infiltration of self-assembled single-molecular layer (SAM layer) is insufficient, which limits the application potential of large-area perovskite batteries.
Trifluoroethanol is added as an additive to the perovskite material, which contains fluorine atomic groups and hydroxy functional groups. By optimizing the perovskite crystallization process and interface wetting, the quality of the perovskite film and the wetting of the SAM layer are improved. .
The photovoltaic characteristics of perovskite batteries are significantly improved, including photoelectric conversion efficiency, open circuit voltage, fill factor and short circuit current density, and the overall performance and stability of the battery are enhanced.
Smart Images

Figure CN119403347A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of perovskite cell preparation, and in particular relates to an additive for a perovskite material, a perovskite cell and a preparation method. Background Art
[0002] Perovskite solar cells are a new type of solar cell that has attracted much attention for its advantages such as high efficiency, low cost and flexible preparation. In perovskite solar cells, the formal structure and the trans structure are two common device structures.
[0003] In the formal structure of perovskite solar cells, light is incident from one side of the transparent conductive substrate, passes through the electron transport layer and reaches the perovskite light absorption layer. After the perovskite layer absorbs light, electron-hole pairs are generated. The electrons are collected by the electron transport layer and transferred to the transparent conductive substrate, and the holes pass through the hole transport layer to the metal electrode, thus forming a photocurrent.
[0004] The main difference between the trans-structured perovskite solar cells and the regular structure is the arrangement order of the functional layers. In the trans-structure, the hole transport layer is located between the transparent conductive substrate and the electron transport layer, while the electron transport layer is located between the perovskite light absorption layer and the metal electrode.
[0005] Compared with formal perovskite solar cells, inverse perovskite solar cells not only have obvious advantages in stability, but also their structure can be better adapted to the traditional crystalline silicon route, so as to prepare more efficient silicon-calcium stacked cells. The SAM layer (self-assembled monolayer) is an important component of inverse perovskite solar cells. Its application in inverse perovskite cells has greatly improved the maximum efficiency of inverse perovskite cells. However, the wettability of the SAM layer is generally not good enough, which restricts its application potential in large-area perovskite cells. Therefore, it is particularly important to effectively solve the above problems and further improve the device performance of inverse perovskite cells.
[0006] Existing solutions include adding a NiOx layer under the SAM layer to form a double hole transport layer to increase the uniformity of the perovskite coating; another example is adding a layer of Al2O3 on the surface of the SAM layer to increase the wettability of the perovskite precursor solution on the surface of the SAM layer. The above methods have single functions, and they all add additional steps to the existing process and introduce additional functional layers, which may have a certain impact on the long-term stability of perovskite solar cells and are not conducive to the long-term stability of perovskites.
[0007] It is necessary to explore methods that do not add additional functional layers and have simple processes, so as to improve the performance of battery devices by optimizing the interface. Summary of the invention
[0008] In order to overcome the above defects, the present invention proposes an additive for perovskite material, a perovskite cell and a preparation method. By adding the additive of the present invention to the perovskite material, the photovoltaic properties of the perovskite cell device can be improved.
[0009] In a first aspect, the present invention provides an additive for a perovskite material, wherein the functional groups of the additive include at least a fluorine atom group and a hydroxyl group.
[0010] Furthermore, the additive is trifluoroethanol.
[0011] In a second aspect, the present invention provides a perovskite precursor, comprising:
[0012] Perovskite materials; and
[0013] The additive according to the first aspect.
[0014] Furthermore, the molar ratio of the perovskite material to the additive is 100:(1-20).
[0015] In a third aspect, the present invention provides a perovskite battery, comprising:
[0016] substrate;
[0017] A first electrode formed on the substrate;
[0018] a first transmission layer formed on the first electrode;
[0019] A perovskite light absorption layer is obtained from the perovskite precursor according to the second aspect, and is formed on the first transmission layer;
[0020] a second transmission layer formed on the perovskite light absorbing layer;
[0021] The second electrode is formed on the second transmission layer.
[0022] Furthermore, the hole transport layer comprises a self-assembled monolayer.
[0023] Furthermore, the self-assembled monolayer comprises:
[0024] At least one of [2-(9H-carbazol-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethyl-9H-carbazol-9-yl)butyl]phosphonic acid and [4-(3,6-dimethoxy-9H-carbazol-9-yl)butyl]phosphonic acid.
[0025] Furthermore, the first transport layer is a hole transport layer; and the second transport layer is an electron transport layer.
[0026] Furthermore, the battery further includes a blocking layer formed on the electron transport layer.
[0027] In a fourth aspect, the present invention provides a method for preparing a perovskite battery, comprising:
[0028] forming a first electrode on a substrate;
[0029] forming a first transmission layer on the first electrode;
[0030] According to the perovskite precursor of the third aspect, a perovskite light absorption layer is formed on the first transmission layer;
[0031] forming a second transmission layer on the perovskite light absorbing layer;
[0032] A second electrode is formed on the second transmission layer.
[0033] Furthermore, the perovskite precursor according to the third aspect forms a perovskite light absorption layer on the first transmission layer, comprising:
[0034] Evenly mixing the perovskite material and the additive to obtain a perovskite precursor;
[0035] coating the perovskite precursor on the first transport layer;
[0036] Annealing is performed at a preset temperature to form a perovskite light absorbing layer.
[0037] Further, the annealing at a preset temperature includes:
[0038] Anneal at 100-180°C for 10-30 min.
[0039] Furthermore, the first transport layer is a hole transport layer; and the second transport layer is an electron transport layer.
[0040] The above one or more technical solutions of the present invention have at least one or more of the following beneficial effects:
[0041] The additive of the perovskite material of the present invention can optimize the perovskite crystallization process by utilizing the fluorine functional group therein, and the quality of the perovskite film is significantly improved. By utilizing the hydroxyl functional group therein, the optimized crystallization interface is improved in wettability on the surface of the hole transport layer through the hydrophilicity of the hydroxyl functional group. Through the combined action of the fluorine atom group and the hydroxyl group, the interface can be optimized and wettability can be facilitated.
[0042] The typical additive is trifluoroethanol, which contains fluorine and hydroxyl functional groups, which can improve the perovskite precursor solution and the wettability on the surface of the SAM layer, and has significant advantages in the preparation of perovskite films over a large area. In addition, trifluoroethanol can be completely evaporated during the annealing process and will not remain in the perovskite film, which will not have an adverse effect on the long-term stability of the perovskite film. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The disclosure of the present invention will become more easily understood with reference to the accompanying drawings. It is easy for those skilled in the art to understand that these drawings are only for illustrative purposes and are not intended to limit the scope of protection of the present invention. In addition, similar numbers in the figures are used to represent similar components, among which:
[0044] Figure 1 is a schematic diagram of the main structure of a perovskite battery according to an embodiment of the present invention;
[0045] Figure 2 It is a schematic diagram of the main process of a method for preparing a perovskite battery according to an embodiment of the present invention;
[0046] Figure 3 It is a schematic diagram of the main process of forming a perovskite light absorption layer according to an embodiment of the present invention.
[0047] Reference numerals list :
[0048] 1. Substrate, 2. First electrode, 3. First transmission layer, 4. Second transmission layer, 5. Second electrode. DETAILED DESCRIPTION
[0049] Some embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0050] The present invention provides an additive for a perovskite material, wherein the functional groups of the additive at least include a fluorine atom group and a hydroxyl group.
[0051] The present invention finds an additive that can be added to the perovskite material. During the crystallization process of the perovskite, the fluorine (-F) functional group can play a key role, so that the crystallization process is optimized, thereby significantly improving the quality of the perovskite film.
[0052] In addition, the additive also contains a hydroxyl functional group. This functional group plays an important role in optimizing the crystallization interface. Through the hydrophilicity of the hydroxyl functional group, the wettability of the perovskite film on the surface of the transport layer, especially the hole transport layer, can be effectively improved. In this way, the crystallization interface is optimized and the bonding force between the film and the transport layer is improved.
[0053] In the additives, the interface performance is further optimized through the combined action of fluorine atom groups and hydroxyl groups. This innovative achievement provides new ideas and methods for the research and application of perovskite materials.
[0054] In one embodiment, the additive is trifluoroethanol.
[0055] The addition of trifluoroethanol can greatly improve the wettability of the perovskite precursor solution and the surface of the hole transport layer such as the SAM layer, and has significant advantages in the preparation of perovskite films over a large area.
[0056] The fluorine functional groups contained in trifluoroethanol can affect the growth and morphology of perovskite crystals, regulate the growth process of perovskite crystals, and prepare dense, pinhole-free, high-quality perovskite films.
[0057] The fluorine functional group contained in trifluoroethanol has good hydrophilicity and improves the interfacial wettability of the hole transport layer.
[0058] Trifluoroethanol is a solvent with a boiling point between 77-80°C, which is lower than the thermal annealing temperature of perovskite. It can be completely evaporated during the perovskite annealing process and will not remain in the perovskite film, which will not have an adverse effect on the long-term stability of the perovskite film.
[0059] The present invention provides a perovskite precursor, comprising:
[0060] Perovskite materials; and
[0061] The additives described.
[0062] The present invention mixes the additive with the perovskite material to obtain a perovskite precursor, which is used to improve the interface of the transport layer, especially the hole transport layer.
[0063] In one embodiment, the molar ratio of the perovskite material to the additive is 100:(1-20).
[0064] In one embodiment, the perovskite material comprises an organic-inorganic hybrid ABX3 type perovskite material, wherein the A-site ions include but are not limited to formamidine (FA + ), methylamine (MA + ), cesium (Cs + ) one or more, B-site ions include but are not limited to lead (Pb 2+ ), tin (Sn 2+ ) and other metal ions, and the X-site ions include but are not limited to iodine (I - ), bromine (Br - ), chlorine (Cl - ) or more halogen atoms.
[0065] The present invention also provides a perovskite battery, referring to Figure 1 ,include:
[0066] Substrate 1;
[0067] A first electrode 2, formed on the substrate;
[0068] A first transmission layer 3, formed on the first electrode;
[0069] A perovskite light absorption layer is obtained according to the perovskite precursor and formed on the first transmission layer;
[0070] A second transmission layer 4, formed on the perovskite light absorption layer;
[0071] The second electrode 5 is formed on the second transmission layer.
[0072] In one embodiment, the perovskite cell is a trans-perovskite cell. The first transport layer 3 is a hole transport layer; the second transport layer 4 is an electron transport layer. Since the wettability of the trans-SAM is generally poor, this will seriously affect the performance of the battery, because poor wettability will lead to poor interface contact, which in turn affects the charge transfer efficiency. Since the additive of the present invention can improve the interface, the additive of the present invention can better solve the wettability problem of the trans-SAM and achieve a higher performance and more stable perovskite cell.
[0073] In one embodiment, the inverse perovskite cell of the present invention further includes a blocking layer formed on the electron transport layer.
[0074] In one embodiment, the hole transport layer includes a self-assembled monolayer (SAM). SAM is a monolayer spontaneously formed at the interface between a solid substrate and a liquid or gas phase, and has the characteristics of self-assembly and orderly molecular arrangement. Due to the ultra-strong control ability of interface chemistry.
[0075] The present invention uses a compound such as trifluoroethanol which contains both a fluorine atom group and a hydroxyl group as an additive to the perovskite precursor solution, which can effectively improve the problem of insufficient wettability of the perovskite solution on the surface of the SAM layer. This is due to the hydrophilicity of the hydroxyl (-OH) functional group in trifluoroethanol. At the same time, due to the positive effect of the fluorine (-F) functional group in trifluoroethanol on the growth and regulation of perovskite crystals, the additive of the present invention can effectively improve the quality of the perovskite film.
[0076] In one embodiment, the self-assembled monolayer is prepared by including but not limited to one of 2PACz ([2-(9H-carbazole-9-yl)ethyl]phosphonic acid), Me-4PACz ([4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid), and MeO-4PACz ([4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid).
[0077] In one embodiment, the first electrode includes an ITO conductive substrate or a FTO conductive substrate.
[0078] The second electrode includes a Cu electrode.
[0079] The electron transport layer comprises C 60 .
[0080] The barrier layer includes a bathocuproine (BCP) layer.
[0081] The present invention also provides a method for preparing a perovskite battery, referring to Figure 2 ,include:
[0082] S1, forming a first electrode on a substrate;
[0083] S2, forming a first transmission layer on the first electrode;
[0084] S3, forming a perovskite light absorption layer on the first transmission layer according to the perovskite precursor;
[0085] S4, forming a second transmission layer on the perovskite light absorption layer;
[0086] S5, forming a second electrode on the second transmission layer.
[0087] In one embodiment, referring to Figure 3 In step S3, forming a perovskite light absorption layer on the first transmission layer according to the perovskite precursor comprises:
[0088] S31, uniformly mixing the perovskite material and the additive to obtain a perovskite precursor;
[0089] S32, coating the perovskite precursor on the first transport layer;
[0090] S33, annealing at a preset temperature to form a perovskite light absorption layer.
[0091] In one embodiment, the annealing at a preset temperature includes:
[0092] Anneal at 100-180°C for 10-30 min.
[0093] In one embodiment, the annealing at a preset temperature includes:
[0094] Anneal at 150°C for 20 min.
[0095] In one embodiment, the perovskite cell is an inverse perovskite cell, the first transport layer is a hole transport layer, and the second transport layer is an electron transport layer.
[0096] The additive of the present invention is more suitable for use in an inverse perovskite battery, improving the interface between the titanium ore light absorption layer and the hole transport layer, and improving the carrier transport efficiency.
[0097] In one embodiment, the step S32 of coating the perovskite precursor on the first transmission layer includes:
[0098] The perovskite precursor is coated on the first transport layer by using one of a spin coating method, a slit coating method, a blade coating method, a screen printing method, and an inkjet printing method.
[0099] It should be pointed out that although the various steps in the above embodiments are described in a specific order, those skilled in the art can understand that in order to achieve the effects of the present invention, different steps do not have to be performed in such an order. They can be performed simultaneously (in parallel) or in other orders. These changes are within the scope of protection of the present invention.
[0100] The present invention is applied to an inverse perovskite battery below, and the effect of improving the electrochemical performance of the battery device is explained through experimental examples.
[0101] Example 1
[0102] ITO is used as the conductive substrate, Me-4PACz is used as the hole transport layer, and FA 85 Cs 15 PbI3 is the perovskite functional layer, C 60 The electron transport layer, BCP and copper are used as the back electrode, and the steps are as follows:
[0103] Step 1: Place the 10×10 cm ITO glass after laser scribing P1 into a cleaning rack, and use a solution with a detergent: deionized water volume ratio of 1:20, deionized water, and anhydrous ethanol to ultrasonically clean it in an ultrasonic machine for 20 minutes, then blow dry with nitrogen for later use.
[0104] Step 2: Weigh 0.5 mg of Me-4PACz ([4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid) and add 1 ml of anhydrous isopropyl alcohol (IPA) solvent in a glove box. After fully dissolving for 12 hours, a precursor solution of the hole transport layer is obtained.
[0105] Step 3: Weigh 11064.2 mg of PbI2, 3508.2 mg of FAI and 935.3 mg of CsI, and add 162.1 mg of MACl to prepare the perovskite material. Then, add 16 ml of DMF and 4 ml of DMSO solvent in the glove box, and add trifluoroethanol as an additive. The molar ratio of the perovskite material to the additive is 100:10. Prepare 20 ml of FACl. 85 Cs 15 PbI3 precursor solution.
[0106] Step 4: The ITO glass cleaned in step 1 was treated with UV ozone for 15 minutes, and the Me-4PACz solution prepared in step 2 was used to prepare a hole transport layer by a slit coating method, and the hole transport layer was prepared by annealing at 100° C. for 10 minutes.
[0107] Step 5: On the surface of the SAM layer obtained in step 4, use the FA prepared in step 3 85 Cs 15 PbI3 precursor solution was used to prepare FA by slit coating method. 85 Cs 15 After coating, the PbI3 film is annealed at 150℃ for 20min to obtain FA 85 Cs 15 PbI3 functional layer film.
[0108] Step 6: Substitute the FA obtained in step 5 85 Cs 15 The PbI3 functional layer film is placed in a sealed box, and the electron transport layer C of appropriate thickness is formed by thermal evaporation. 60 , and the barrier layer BCP are evaporated in sequence. Then, the substrate after laser scribing P2 is used, and the thermal evaporation equipment is used again to deposit the Cu electrode of appropriate thickness. Finally, laser scribing P3 and local edge cleaning are performed to obtain an effective area of 49cm 2 FA 85 Cs 15 PbI3 inverse perovskite solar cells.
[0109] Example 2
[0110] The difference between Example 2 and Example 1 is only that:
[0111] (1) In step 3, trifluoroethanol is added as an additive, and the molar ratio of the perovskite material to the additive is 100:1.
[0112] (2) In step 5, after coating, annealing is performed at 100°C for 30 minutes.
[0113] Example 3
[0114] The difference between Example 3 and Example 1 is only that:
[0115] (1) In step 3, trifluoroethanol is added as an additive, and the molar ratio of the perovskite material to the additive is 100:20.
[0116] (2) In step 5, after coating, annealing is performed at 180°C for 10 minutes.
[0117] Comparative Example 1
[0118] The difference between Comparative Example 1 and Example 1 is only that:
[0119] (1) In step 3, trifluoroethanol was not added as an additive.
[0120] Comparative Example 2
[0121] The difference between Comparative Example 2 and Example 1 is only that:
[0122] (1) In step 3, trifluoroethanol is replaced with lithium fluoride (LiF).
[0123] Comparative Example 3
[0124] The difference between Comparative Example 3 and Example 1 is only that:
[0125] (1) In step 3, trifluoroethanol is replaced with ethanol (C2H6O).
[0126] Comparative Example 4
[0127] The difference between Comparative Example 4 and Example 1 is only that:
[0128] (1) Trifluoroethanol is replaced by a combination of lithium fluoride and ethanol, with the molar ratio of the two being 1:1.
[0129] The inverse perovskite solar cells obtained in Examples 1 to 3 and Comparative Examples 1 to 4 were tested, and the test results are shown in Table 1. The device performance results show that the addition of trifluoroethanol significantly improves the photovoltaic characteristics of the device.
[0130] Table 1 Photovoltaic performance parameters of perovskite solar modules obtained in the examples and comparative examples
[0131]
[0132] The present invention improves the problem of insufficient wettability of the perovskite solution on the surface of the SAM layer by adding a trifluoroethanol component having hydroxyl (-OH) and fluorine (-F) functional groups into the perovskite material, thereby improving the electrochemical performance of the device.
[0133] As can be seen from the data in Table 1, Examples 1-3 to which trifluoroethanol is added all have a certain improvement in electrochemical performance over the comparative battery. First of all, let’s talk about the photoelectric conversion efficiency (Power Convers ion Efficiency, PCE), which is one of the most important performance parameters of perovskite batteries. The core problem of trans-perovskite batteries is that there are defects at the interface between the perovskite and the transport layer, which leads to serious energy loss and restricts efficiency improvement. The present invention uses trifluoroethanol as a preparation method for additives, which greatly improves the wettability of the perovskite precursor solution on the SAM layer, which has a positive effect on the large-area coating preparation of perovskite components containing SAM layers. In addition, the fluorine (-F) functional group contained in trifluoroethanol can regulate the crystal growth of perovskite to obtain a perovskite film with high crystallinity, no pinholes, and a dense perovskite film. Finally, because trifluoroethanol has a boiling point below 100°C, it can evaporate and disappear during the thermal annealing of the perovskite, and will not remain in the perovskite film, and will not affect the long-term stability of the perovskite battery. Therefore, after the additive is mixed into the perovskite material, the prepared battery is conducive to the rapid transmission of electrons and holes, reduces energy loss, and increases the life of carriers. Therefore, the improvement of PCE means that the preparation process of the perovskite film has been optimized, and the crystallinity and uniformity of the perovskite film have been improved. The increase in PCE directly reflects that the battery is more efficient in generating electrical energy under light, that is, more light energy is converted into electrical energy, indicating that the overall performance of the battery has been improved.
[0134] Next, the open circuit voltage (V OC ,Open-Circuit Voltage) improvement. OC It is the voltage of a solar cell in an open circuit state (i.e. when there is no current flowing in the circuit). It is one of the important indicators for measuring battery performance. OC The improvement directly reflects that the maximum voltage that the battery can generate under illumination is higher, which generally means that the overall performance of the battery has been enhanced. Since the present invention improves the interface between the perovskite and the hole transport layer, the energy loss of photogenerated carriers during transmission through non-radiative pathways (such as thermal release, defect recombination, etc.) is reduced. By improving the interface quality of the perovskite battery, reducing defects and improving wettability, the non-radiative recombination probability can be reduced, thereby improving VOC.
[0135] The following describes the improvement of the fill factor (FF). The larger the fill factor value, the closer the output characteristics of the solar cell are to a rectangle, and the higher the photoelectric conversion efficiency of the cell. Improving the FF of the device is an effective way to improve the efficiency of the device. The performance of the titanium ore cell is greatly affected by the interface quality. The key factor in preparing high-performance perovskite solar cells is to improve the charge transfer at the perovskite interface. The present invention improves the fill factor, one of the important parameters that characterize the quality of solar cells, by improving the interface quality of the perovskite layer and the hole transport layer.
[0136] The following describes J SC The short-circuit current density (J SC ,Short-Circuit Current Density) is one of the important indicators for evaluating the performance of perovskite batteries. Under standard test conditions, J SC The value can be compared with other performance indicators (such as open circuit voltage V OC , fill factor FF and photoelectric conversion efficiency PCE) to comprehensively evaluate the performance of the battery.
[0137] At zero voltage, the current becomes the photocurrent J SC , represents the current generated by the solar cell under poor lighting conditions, J SC The larger it is, the greater the current that the battery can generate under the same lighting conditions, and the higher the photoelectric conversion efficiency. SC The improvement usually means that the perovskite cell has an enhanced ability to absorb light, as well as improved generation, separation and transmission efficiency of photogenerated carriers. This is due to the fact that the present invention improves the interface quality of the perovskite layer and the hole transport layer, thereby improving the interface quality of the perovskite layer and the hole transport layer, and the generation, separation and transmission efficiency of photogenerated carriers.
[0138] It can be seen from this that the application of the additive of the present invention in perovskite batteries can significantly and comprehensively improve the electrochemical performance of perovskite batteries, which not only provides new ideas for the research and development of perovskite batteries, but also contributes to the development of my country's new energy industry.
[0139] The present invention acts on a perovskite precursor solution. The method is applicable to perovskites of different systems, and can be particularly well extended to a transverse large-area component containing a SAM layer.
[0140] First, the present invention can effectively improve the wettability of the perovskite solution on the surface of the SAM layer. In traditional technologies, the wettability of the perovskite solution on the surface of the SAM layer is often poor, which limits the preparation quality and efficiency of the perovskite film.
[0141] Secondly, the present invention greatly expands the possibility of preparing perovskite films over a large area, which means that large-area perovskite films can be produced more efficiently while maintaining high quality, which is of great significance for practical applications.
[0142] In addition, the present invention can also improve the crystallization process of the perovskite film, thereby preparing a high-quality perovskite film. In the prior art solutions, the crystallization process of the perovskite film often has certain problems, resulting in poor film quality. The present invention optimizes the crystallization process, so that the prepared perovskite film has higher quality.
[0143] It is worth mentioning that the additives used in the present invention can evaporate during the thermal annealing process of perovskite and will not remain in the perovskite film. This feature not only ensures the long-term stability of the perovskite battery, but also achieves three goals with one stone, that is, it simultaneously solves the problems of perovskite film preparation, crystallization process optimization and interface wettability.
[0144] In contrast, the existing technical solutions introduce additional processes and increase the complexity of the process. This not only increases the production cost, but may also have a certain impact on the long-term stability of perovskite solar cells. At the same time, the introduced additional functional layer has a single function and can only improve the wettability of the SAM surface in most cases, but cannot improve the crystallization process of perovskite and improve the quality of perovskite film.
[0145] The present invention abandons the traditional method of adding functional layers, and instead optimizes the structure of the perovskite battery through a simple process flow.
[0146] By modifying the composition of the original perovskite light absorption layer, the electrochemical performance of the battery can be further improved.
[0147] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
Claims
1. An additive for perovskite material, characterized in that: The functional groups of the additive include at least a fluorine atom group and a hydroxyl group.
2. The additive according to claim 1, characterized in that The additive is trifluoroethanol.
3. A perovskite precursor, characterized in that: include: Perovskite materials; as well as The additive according to claim 1 or 2.
4. The precursor according to claim 3, characterized in that The molar ratio of the perovskite material to the additive is 100:(1-20).
5. A perovskite battery, characterized in that: include: substrate; A first electrode formed on the substrate; a first transmission layer formed on the first electrode; A perovskite light absorbing layer is obtained from the perovskite precursor according to claim 3, and is formed on the first transmission layer; a second transmission layer formed on the perovskite light absorbing layer; The second electrode is formed on the second transmission layer.
6. The battery according to claim 5, characterized in that The first transport layer is a hole transport layer; the second transport layer is an electron transport layer.
7. A method for preparing a perovskite battery, characterized in that: include: forming a first electrode on a substrate; forming a first transmission layer on the first electrode ; According to the perovskite precursor of claim 3, a perovskite light absorption layer is formed on the first transmission layer; forming a second transmission layer on the perovskite light absorbing layer; A second electrode is formed on the second transmission layer.
8. The method according to claim 7, characterized in that According to the perovskite precursor of claim 3, forming a perovskite light absorption layer on the first transmission layer comprises: Evenly mixing the perovskite material and the additive to obtain a perovskite precursor; coating the perovskite precursor on the first transport layer; Annealing is performed at a preset temperature to form a perovskite light absorbing layer.
9. The method according to claim 8, characterized in that The annealing at a preset temperature includes: Anneal at 100-180°C for 10-30 min.
10. The method according to any one of claims 7 to 9, characterized in that: The first transport layer is a hole transport layer; the second transport layer is an electron transport layer.